CFO narcissism and audit fees: Evidence from listed companies in China - Rui Xiang; Congmin Song (China Journal of Accounting Research, 2021)
This paper examines the effects of CFO narcissism on audit fees in China. Using the size of CFO signatures in annual audit reports to measure individual narcissism, we find that CFO narcissism is associated with higher audit fees. We find empirical evidence that CFO narcissism significantly increases the audit fees of listed companies, and this effect is stronger in state-owned enterprises. This paper also explores the mediating effects of financial information and the engagement of prestigious Big-4 and Big-10 firms. The results show that companies with narcissistic CFOs have lower quality financial information and prefer more prestigious firms, which leads to higher audit fees. This research highlights the importance of CFO narcissism in corporate performance and provides new evidence that will be useful for listed companies that plan to hire senior executives.
Keywords: 650; CFO Narcissism; Audit Fees; Property Rights; Fee Premium